THE EFFECT OF RISK PERCEPTION, RETURN EXPECTATIONS, FINANCIAL SELF-EFFICACY, AND FINANCIAL INCLUSION ON STUDENTS’ INTEREST IN STOCK INVESTMENT(A study on active undergraduate accounting students of the 2021 cohort at universities across Bali) - Ni Kadek Brenda Cindy Manika; Ni Putu Sri Harta Mimba (ADISAM Publisher, 2025)
Students’ interest in stock investment has become an important concern in order to increase the participation of the younger generation in the capital market. This study aims to analyze the effect of risk perception, return expectations, financial self-efficacy, and financial inclusion on students’ interest in stock investment. This study uses the Theory of Planned Behavior (TPB) approach. The population in this study consists of active undergraduate (S1/D4) Accounting students of the 2021 cohort from four universities in Bali, namely Mahasaraswati University, Udayana University, Bali State Polytechnic, and the Indonesian Hindu University, with a total of 641 students. The sample was obtained using the purposive sampling method, consisting of 246 respondents. The data analysis technique used is multiple linear regression with the assistance of SPSS software. The results of the study show that: (1) risk perception has a positive and significant effect on students’ interest in stock investment; (2) return expectations also have a positive and significant effect; (3) financial self-efficacy has a negative effect on investment interest; and (4) financial inclusion has a positive effect on students’ interest in stock investment.